KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM SMA NEGERI 5 UNGGULAN PAREPARE - Asnandar Abubakar (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
Teacher’s competencies are a key to the transformation of understanding and religious experience for students. They are pedagogical, personal, social, professional, and leadership competency. The study aims at knowing the reality of religious teacher’s competency in boarding schools and supporting and obstacle factors in improving their competency. It used a qualitative approach and data were collected through interviews, observation, and document review. The object of study was the boarding school educational unit, namely State Senior High School (MAN) 5 favorite in Parepare. The results of the study illustrated that Islamic education (PAI) teachers have competencies and skills as determined by the government such as the ability to motivate and protect students with different characters, having administrative skills in managing instructional learning materials, capability to read class situations when applying or using learning methods, to interpret learning programs to students and to deliver learning effectively and efficiently. The programs of religious teachers’ competency improvement include through the support of Subject Teacher Forum (MGMP) and in house training activities.